TIPOLOGI BUNUH DIRI DALAM NOVEL SAN FRANCISCO: KAJIAN SOSIOLOGI SASTRA - Nurul Lathifah; Kurnia Rachmawati; Arju Susanto (Universitas Negeri Makassar, 2023)
Typology Suicide in the San Francisco Novel: A Study of Literary Sociology. of This study aims to describe and analyze the typology of suicide based on the theory of sociologist Emile Durkheim in the novel San Francisco by Ziggy Zezsyazeoviennazabrizkie. The method used in this research is the descriptive qualitative method. The author carried out the study in two stages, namely data collection and data analysis. The stages of data collection were completed in four ways: reading, recording, and processing data via textual dialogs in the novel. Furthermore, the writer will also describe aspects, facts, and the types of Emile Durkheim's suicide, which will be presented in the form of dialogue text data in a structured manner according to the novel by using the study of sociology of literature. Based on the results of the study, it shows that in the novel San Francisco by Ziggy Zezsyazeoviennazabrizkie, there are three types of suicide according to Emile Durkheim, including egoistic suicide, altruistic suicide, and anomic suicide.